Karyotype and NOR conservatism with heterochromatin reorganization in Neotropical Bryconids - Almeida-Toledo, L. F.; Bigoni, A. P.; Bernardino, G.; Foresti, F. [UNESP]; Toledo-Filho, S. A. (Firenze University Press, 1996)
Cytogenetic studies on Bryconid fishes have shown the occurrence of karyotype and NOR conservatism and heterochromatin reorganization. The present data on three species representative of the migratory genus Brycon corroborate the hypothesis according to which conservative patterns of karyotypic evolution can be related to high levels of vagility and large populational size in Neotropical freshwater fishes.
Keywords: Brycon; Characidae; Cytogenetics; Heterochromatin; NOR